Cubic to tetragonal martensitic transformation in a thin film elastically constrained by a substrate - Seol, D. J.; Hu, S. Y.; Li, Y. L.; Chen, L. Q.; Oh, K. H. (Metals and materials international, 2003)
A 3-dimensional phase-field model is developed to describe the cubic to tetragonal martensitic phase transformation in a thin film attached to a substrate. Elasticity solutions are derived for both elastically anisotropic and isotropic thin films with arbitrary domain structures, subject to the mixed boundary conditions for stress-free and constrained states. The model is applied to an Fe-31%Ni alloy system. The nucleation process as well as the final domain structure strongly depends on the substrate constraint. At a smaller undercooling, the increased strain energy effect results in a lower volume fraction of martensite, a finer domain structure and a longer nucleation period.